Unraveling The Future: Examining How Financial Performance and Company Value Shape The Destiny of Tech Giants - Noval Adib; Rizky Aditya Nugraha; Intan Lifinda Ayuning Putri (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to examine the effect of which variables (financial performance and firm value) are better in explaining bankruptcy prediction in technology sector companies. Methodology/approach: This research is an exploratory study using a population of companies in the technology sector listed on the Indonesia Stock Exchange. Samples were taken in the 2018-2022 period using purposive sampling techniques. The analysis technique used regression analysis with IBM SPSS 24 software. Findings: While firm value may not always predict a tech company's fate, financial performance stands as a critical indicator of potential bankruptcy. This study underscores the importance of prioritizing sound financial health over valuation when assessing risks in the tech sector. Practical and Theoretical contribution/Originality: This finding confirms that the information generated by the stock market is not immediately responded to by investors. This indicates that the stock market in Indonesia is still classified as semi-efficient. Research Limitation: The number of company samples is still limited. This happens because many companies do not have complete data. There are technology companies that have not been listed on the IDX for 5 years so they cannot be used in testing.